Cheap-Talk Advertising and Misrepresentation in Vertically Differentiated Markets - Gardete, Pedro M. (Marketing Science, 2013)
I consider a cheap-talk model in which a firm has a chance to communicate its product quality to consumers. The model describes how advertising can be both informative to consumers and profitable for the firm through its content in a vertically differentiated market. I find that advertising content may be effective in inducing search even if incentives for misrepresentation exist. In particular, a firm with an undesirable (low-quality) product is able to attract consumers who would have not incurred a search cost had they known its true quality. In this case, a semiseparating equilibrium occurs where the lowest firm types pool upward in order to increase the expected product quality while simultaneously signaling that the product is affordable. Although consumers always benefit from truth in advertising, total welfare may decrease if an undesirable firm is required to reveal its type. Finally, I show that the extent to which misrepresentation can take place increases with the cost of advertising coverage.